Renewable Energy Financing and Sustainable Industrial Development in Nigeria - Asemota, Franklin Famous; Olokoyo, Felicia Omowunmi (International Journal of Energy Economics and Policy, 2022)
Due to the inability of renewable and non-renewable sources of energy to meet the ever-increasing industrial energy need in Nigeria, there is therefore need to explore various financing option available to execute renewable energy project that will contribute to the energy basket which will sustainably impact industrial development in Nigeria. Obtaining secondary data from World development indicator from 1980 to 2021, the study utilized the auto-regressive distributed lag method to estimate the long run impact of renewable energy financing and sustainable industrial development in Nigeria. The findings reveal that the use of external debt for financing renewable energy as well the use of energy from Combustible waste source and alternate nuclear source significantly and positively determines the development of the industrial sector in Nigeria. while the use of taxation and donation to fund renewable energy as well as the use of energy source from hydroelectric were not contributing significantly to sustainable industrial development in Nigeria. The study further recommends that relevant framework that will make investment in renewable energy as well as the utilization of renewable energy to be attractive to various stakeholders in Nigeria should be established. The underlying downside risk in renewable energy utilization and financing must be address so as to mobilize sufficient private sector investment needed to drive sustainable industrial development in Nigeria